Die Akten des Kaiserlichen Reichshofrats (RHR) – Serie II (Erich Schmidt Verlag GmbH & Co. KG, 2022)
The Aulic Council, together with the Imperial Chamber Court, exercised supreme jurisdiction in the Holy Roman Empire on behalf of the Emperor. It also acted as the supreme feudal court, as an advisory body to the head of the Empire and as the administrative organ of the exclusively imperial rights, which for example concerned matters of status and privileges. The archival heritage of the Aulic Council is kept in Vienna by the Austrian State Archives. The holdings extend over approximately 1.3 kilometres of shelving with tens of thousands of files containing first-rate sources on the history of Central Europe in the early modern period.